Global disease burden of breast cancer attributable to high fasting plasma glucose: a comprehensive analysis from the global burden of disease study - Zhang, Jing; He, Jiawei; Lu, Yunyan; Lan, Tian (Frontiers in Endocrinology, 2025)
BackgroundHigh fasting plasma glucose (HFPG) has been identified as one of the risk factors associated with the development of breast cancer. The worldwide distribution of breast cancer attributable to HFPG was not comprehensively investigated.MethodsWe utilized the data from the Global Burden of Disease Study 2021 to explore HFPG-related breast cancer deaths, disability adjusted life years (DALYs) and corresponding age-standardized rates (ASRs). The average annual percentage change (AAPC) and the estimated annual percentage change (EAPC) were employed to evaluate the temporal trend.ResultsThe global effect of HFPG resulted in nearly 30,570 breast cancer deaths and 819,550 DALYs in 2021, representing an age-standardized deaths rate (ASMR) of 0.66 (95% UI -0.19-1.57) and an age-standardized DALYs rate (ASDR) of 18.05 (95% UI -5.31-42.71). In the regions with low, low-middle, and middle SDI, the ASRs of HFPG-related breast cancer increased significantly over time. The highest ASMR and ASDR were observed in several countries, such as Palau, American Samoa, Cook Islands, Marshall Islands, and United Arab Emirates. There was a positive correlation between ASRs and Socio-Demographic Index (SDI) in countries where SDI was below 0.75. The escalation in death and DALYs was primarily driven by epidemiological change and population growth in low, low-middle, middle SDI regions.ConclusionsSubstantial disparities exist across diverse regions in breast cancer burden attributed to HFPG. It is urgent to regulate glycemic levels, improve healthcare infrastructures, and provide cost-effective care in less developed and developing countries that endure a disproportionately heavier health burden.